Small molecules modified biomimetic gelatin/hydroxyapatite nanofibers constructing an ideal osteogenic microenvironment with significantly enhanced cranial bone formation - Li D (Dove Medical Press, 2018)
Daowei Li,1,2 Kai Zhang,2 Ce Shi,1,2 Lijun Liu,1 Guangxing Yan,1 Cangwei Liu,1 Yijun Zhou,1 Yue Hu,1 Hongchen Sun,3 Bai Yang2 1Department of Oral Biology, Jilin Provincial Key Laboratory of Tooth Development and Bone Remodeling, School and Hospital of Stomatology, Jilin University, Changchun, People’s Republic of China; 2Department of Oral Pathology, Liaoning Province Key Laboratory of Oral Disease, School and Hospital of Stomatology, China Medical University, Shenyang, People’s Republic of China; 3Department of Multiscale Diagnosis and Treatment Chemistry, State Key Laboratory of Supramolecular Structure and Materials, College of Chemistry, Jilin University, Changchun, People’s Republic of China Background: Repair of nonunion critical-sized bone defects is a significant clinical challenge all over the world. Construction of osteogenic microenvironment that provides osteoconductive and osteoinductive signals is a leading strategy. Materials and methods: In the present study, ascorbic acid (AA) and β-glycerophosphate disodium salt hydrate (β-GP) modified biomimetic gelatin/hydroxyapatite (GH) nanofibrous scaffolds were developed by electrospinning. Then the scaffolds were crosslinked by N-hydroxysulfo-succinimide sodium salt (NHS) and 1-(3-Dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC). The morphology of the non-crosslinked and crosslinked scaffolds was evaluated by scanning electron microscope (SEM). Fourier transform infrared spectroscopy (FT-IR) was used to assess the interacting model between the small molecules and GH scaffold. Then MTT, Alamar Blue, and CCK8 assays were used to investigate the biocompatibility of the various crosslinked scaffolds. Subsequently, the osteogenic genes expression of bone marrow stromal cells (BMSCs) cultured on the scaffolds were detected by quantitative reverse transcription polymerase chain reaction (qRT-PCR). Finally, the crosslinked scaffolds were implanted in a rat calvarial defect model to assess the osteogenic effects in vivo. Results: SEM results showed that the various scaffolds presented extracellular matrix (ECM)-like fibrous porous structure. (FT-IR) spectrum indicated that AA and β-GP were covalently bonded with GH scaffolds. The MTT, Alamar Blue, and CCK8 assays demonstrated that all the scaffolds can support BMSCs’ growth well. The qRT-PCR results showed that the expression level of Alp and Runx2 in BMSCs on GH/A/B scaffold was about 3.5- and 1.5-fold, respectively, compared with that of GH group on day 7. The results also showed that AA- and β-GP-modified GH scaffolds can significantly induce the higher levels of osteogenic gene expression in a temporal specific manner. Importantly, AA and β-GP synergistically promoted osteoblast differentiation in vitro and dramatically induced bone regeneration in vivo. Impressively, AA and β-GP dual modified GH nanofibrous scaffold could serve as a template for guiding bone regeneration and the bone defects were almost repaired completely (94.28%±5.00%) at 6 weeks. Besides, single AA or β-GP-modified GH nanofibrous scaffolds could repair 62.95%±9.39% and 66.56%±18.45% bone defects, respectively, at 12 weeks in vivo. In addition, AA and β-GP exhibit an anti-inflammatory effect in vivo. Conclusion: Our data highlighted that, AA, β-GP, and GH nanofibers created a fine osteoconductive and osteoinductive microenvironments for bone regeneration. We demonstrated that AA and β-GP dual modified GH nanofiber is a versatile bone tissue engineering scaffold. Keywords: microenvironment, bone tissue engineering, β-glycerophosphate disodium salt hydrate, ascorbic acid, gelatin, hydroxyapatite nanofibers